Isolation and characterization of a novel exopolysaccharide secreted by Lactobacillus mucosae VG1. (1st October 2019) - Fagunwa, Omololu; Ahmed, Hafiz I.; Sadiq, Sohaib; Humphreys, Paul N.; McLay, Neil; Laws, Andrew P.
Abstract: A novel strain of Lactobacillus mucosae was isolated from a faecal sample of an individual who had adhered to a strict vegetarian diet for nine years. The strain displayed a ropy character when grown on plates and generated a relatively small amount (62 mg/L) of an exopolysaccharide (EPS) when grown in broth culture. The EPS eluted from a size exclusion chromatography column as a single band with a weight average molecular mass of 1.51 × 10 4 g/mol. Monomer analysis and sugar absolute configuration analysis confirmed that the EPS was a D-galactan. Using linkage analysis in combination with 1D and 2D-NMR spectroscopy, with spectra being recorded for both the native EPS and for the products generated by Smith degradation of the EPS, the following structure was determined for the repeat unit of the polysaccharide:Image 1 This is a novel D-galactan and represents the first structure for an EPS produced by a strain of Lactobacillus mucosae to be reported. Graphical abstract: Image 1 Highlights: Isolation of a novel, potentially probiotic, strain of L. mucosae ( L mucosae VG1) . Production and isolation of an exopolysaccharide from L mucosae VG1. Characterization of the exopolysaccharide from L mucosae VG1; a novel D-galactan.